2023
DOI: 10.1089/apc.2022.0178
|View full text |Cite
|
Sign up to set email alerts
|

Tilting the Scale: Current Provider Perspectives and Practices on Breastfeeding with HIV in the United States

Abstract: The risk of vertical transmission from breastfeeding with HIV (BFHIV) has been found to be very low in optimal scenarios with sustained maternal viral suppression during pregnancy and postpartum. Medical providers must account for the risk of this serious adverse event alongside parental autonomy, breastfeeding benefits, and patient values. To assess provider practices, comfort, and challenges with BFHIV, an online mixed-method survey was sent to breastfeeding and HIV provider listservs from June to July 2021.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For example, although maternal human immunodeficiency virus (HIV) infection has long been considered a contraindication to BF, the World Health Organization recommends antiretroviral therapy, which greatly reduces postnatal transmission of HIV through maternal HM, and supports BF as long as desired. 26 Additionally, few medications are fully incompatible with BF, and infant age and health status, lactational stage, dosage, and timing of medication may alter the risk profile for an individual infant; the InfantRisk Center at Texas Tech University Health Sciences Center (https://infantrisk.com/) provides individualized, up-to-date guidance. Provision of maternal HM to infants whose parents engage in substance use is highly variable, and we would refer providers to the Academy of Breastfeeding Medicine's protocol on managing BF in the case of substance use disorder.…”
Section: Hm In the Hospital Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, although maternal human immunodeficiency virus (HIV) infection has long been considered a contraindication to BF, the World Health Organization recommends antiretroviral therapy, which greatly reduces postnatal transmission of HIV through maternal HM, and supports BF as long as desired. 26 Additionally, few medications are fully incompatible with BF, and infant age and health status, lactational stage, dosage, and timing of medication may alter the risk profile for an individual infant; the InfantRisk Center at Texas Tech University Health Sciences Center (https://infantrisk.com/) provides individualized, up-to-date guidance. Provision of maternal HM to infants whose parents engage in substance use is highly variable, and we would refer providers to the Academy of Breastfeeding Medicine's protocol on managing BF in the case of substance use disorder.…”
Section: Hm In the Hospital Settingmentioning
confidence: 99%
“…To best support BF parents, including those of vulnerable infants most in need of HM, clinicians should familiarize themselves with up‐to‐date guidance from the Centers for Disease Control and Prevention and the American Academy of Pediatrics on contraindications for providing maternal HM, 7,24,25 which may vary based on available resources and circumstances. For example, although maternal human immunodeficiency virus (HIV) infection has long been considered a contraindication to BF, the World Health Organization recommends antiretroviral therapy, which greatly reduces postnatal transmission of HIV through maternal HM, and supports BF as long as desired 26 . Additionally, few medications are fully incompatible with BF, and infant age and health status, lactational stage, dosage, and timing of medication may alter the risk profile for an individual infant; the InfantRisk Center at Texas Tech University Health Sciences Center (https://infantrisk.com/) provides individualized, up‐to‐date guidance.…”
Section: Hm In the Hospital Settingmentioning
confidence: 99%
“…Historically, families living with HIV in the United States have struggled to navigate infant feeding in the absence of more guidance. Research with health care providers demonstrated that clinicians perceived White patients with HIV faced fewer barriers to breastfeeding than patients with other racial identities (Lai et al, 2023). Lai et al (2023) found providers had a range of management styles from patients making informed feeding choices to paternalism.…”
mentioning
confidence: 99%
“…Research with health care providers demonstrated that clinicians perceived White patients with HIV faced fewer barriers to breastfeeding than patients with other racial identities (Lai et al, 2023). Lai et al (2023) found providers had a range of management styles from patients making informed feeding choices to paternalism. As nurses, we have an important role in educating and advocating for families living with HIV, so they can make informed infant feeding choices.…”
mentioning
confidence: 99%